Canadian Access to Information and Journalism: Obstacles and Opportunities - Margaret Thompson; Elyse Amend; Luisa Marini (Facts & Frictions)
The Canadian federal Access to Information Act (ATIA) is an essential yet inadequate piece of legislation that, in theory, helps facilitate democratic engagement. Making use of this legislation is an essential way for journalists to hold power to account; to provide the public with newsworthy information; to illuminate government officials’ decision-making processes; to verify information gained from other sources; and to provide context for their audiences. However, multiple challenges involved in navigating the federal ATI system pose significant setbacks for journalists. As a result, ATI is not being used to its fullest extent, the quality of journalism being produced is hampered by incomplete information, and the ability of citizens to make informed choices in their lives and in the political sphere is obstructed. Through interviews with 17 Canadian journalists, this research investigates the benefits and barriers federal ATI poses to their work. Its results point to a broken system rife with practical and ideological hurdles that have caused journalists to use it as a “last resort,” or have motivated them to take an information advocacy approach in their reporting.